Queering education in the Deep South - Strunk, Kamden K. (Research in queer studies., 2018)
"This volume explores education in the Deep South, with a focus on LGBTQ students and educators, and on queer theoretical perspectives in education. The topics in this volume include teaching LGBTQ issues and queer studies in the Deep South, educational policy and practice in the Deep South as related to queer issues, and efforts to introduce queer literature to libraries and queer collections to archives. Authors in this volume examine what realities exist in education in the U.S. South currently, and what possibilities might be imagined in the future" --